5t-2=3t-8+8t

Simple and best practice solution for 5t-2=3t-8+8t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5t-2=3t-8+8t equation:


Simplifying
5t + -2 = 3t + -8 + 8t

Reorder the terms:
-2 + 5t = 3t + -8 + 8t

Reorder the terms:
-2 + 5t = -8 + 3t + 8t

Combine like terms: 3t + 8t = 11t
-2 + 5t = -8 + 11t

Solving
-2 + 5t = -8 + 11t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-11t' to each side of the equation.
-2 + 5t + -11t = -8 + 11t + -11t

Combine like terms: 5t + -11t = -6t
-2 + -6t = -8 + 11t + -11t

Combine like terms: 11t + -11t = 0
-2 + -6t = -8 + 0
-2 + -6t = -8

Add '2' to each side of the equation.
-2 + 2 + -6t = -8 + 2

Combine like terms: -2 + 2 = 0
0 + -6t = -8 + 2
-6t = -8 + 2

Combine like terms: -8 + 2 = -6
-6t = -6

Divide each side by '-6'.
t = 1

Simplifying
t = 1

See similar equations:

| 3x(5)+3=18 | | m^2+7m+5=0 | | 10t-4t=-11 | | 2x+19=8x-41 | | 12p+3q-5p+8q= | | 3a-b+c=10 | | 16x+8=32x+16 | | 1.055=x^15 | | x^2+7x=-2x+10 | | -a+4a=9+8a+6 | | .5(x+9)-3=4 | | 29-(x+7)=6x-6 | | 2a+3b-c=-2 | | 4.95x+0.10=120 | | 7(x+5)+1=5 | | (x+9)-3=4 | | x(3)+y(8)=108 | | 3e^2+4e-4=0 | | 3c+5=6c+2 | | x^2-16x+12=2 | | x-9-3=4 | | 19c+3d-7c+5d= | | 12-5x+y=-7y+11+18x | | a+2b+c=36 | | 10k+5m=80 | | 4x+5=360 | | n^2+18n+65=9 | | -1x/10= | | 5(3x-7)-6=9(x-3)+4 | | Z-5z=7z-9-7 | | x+y(2)=30 | | 2x+31+8x+9=180 |

Equations solver categories